THE RELATIONSHIPS OF CASH FLOWS: EVIDENCE FROM LATVIAN COMPANIES - Subatnieks, Kārlis (Ekonomika, 2014)
The paper deals with the subject of relationships among the different cash flows, as well as earnings, of a company. The aim of the paper is to establish the direction and strength of mutual relationships between different cash flow measures, as well as with earnings, and to provide recommendations for the prediction of future cash flows and earnings. The methods of the research include content analysis, the calculation of relative indicators, average and median measures, as well as regression and correlation analysis. There is an empirical study of the data of 52 Latvian companies, which has resulted in testing the hypotheses put forward and substantiated in the paper. A typical Latvian enterprise relies on the operating cash flow to create the investing cash flow and does not need to rely on the external sources of financing. The author concludes that investment does pay, and, based on the assessment of results of the developed model, the investing cash flow should be used in cash flow prediction, while it should not be used in earnings prediction. The increase in financing cash flow causes a company investments to increase.